PARADIGMA MEMBANGUN GENERASI EMAS 2045 DALAM PERSPEKTIF FILSAFAT PENDIDIKAN - Dongoran, Faisal R (TABULARASA, 2014)
The quality of a society has a strategic relationship with the world of education, primary school world, because in it there is a genuine effort on education to prepare the next generation of skilled and have the sciences with based on faith and piety to God Almighty in a broad context. Generation question is